(untitled) (International relations and international law Journal, 2018)
The article describes the role of the socio-historical and natural and geographical conditions in lawmaking. Respectively, in article are considered questions of influence of objective factors on lawmaking, communication of legislative activity with public conditions and their interdependence. In article it is emphasized that objective regularities which were created for many years and don’t depend on will and consciousness of person and legislator are the bases of lawmaking. In article are analyzed extents of influence of these objective regularities on lawmaking of the country, on formations of contents of laws. Also, in article are considered the essences of social-historical and natural-geographical conditions, their value, need to consider them in the process of lawmaking. Key words: Parliament, law, legislative activity, legislator, deputy, society, objective factor, social-historical and natural-geographical conditions, culture, mentality, traditions.